The impact of bilateral brachial-ankle pulse wave velocity difference on cardiovascular disease and all-cause mortality - Zheng, Mengyi; Zhang, Xinyuan; Zhao, Quanhui; Chen, Shuohua; Guo, Xinying; Wang, Chi; Jonas, Jost B.; Wu, Shouling; Guo, Caixia (Frontiers in Cardiovascular Medicine, 2023)
Background: This study aims to investigate the association between an elevated bilateral pulse wave velocity difference (BPWVD) and cardiovascular diseases (CVDs) and all-cause mortality.Methods: 38,356 participants were included. A multivariable Cox proportional hazards regression was used to assess the association between high BPWVD and the increased risk of CVDs and all-cause mortality by calculating hazard ratios with 95% confidence intervals (CIs).We detected 1,213 CVDs in 6.19 years (mean), including 886 cases of CI, 105 cases of ICH, and 222 cases of MI, along with 1,182 cases of all-cause mortality.The median BPWVD was 42 cm/s (19-80 cm/s). After adjusting for all confounders and baseline baPWV, we observed that higher risk of CVDs, MI, and all-cause mortality that appeared to be associated with BPWVD per standard deviation increase. HRs (95% CI) were 1.